Avaliação de programas de mudança de comportamento usando a ferramenta RE-AIM: um estudo de revisão sistemática - Konrad, Lisandra (2018)
A systematic review was carried out to evaluate the extent to which behavioral change programs with emphasis on physical activity and/or healthy eating in Brazilian adults and/or elderly people report factors related to internal and external validity using the RE-AIM framework. Twenty six studies were selected from the Medline/Pubmed, Lilacs, Science Direct, Web Of Science, Scopus, PsycINFO and Google Academic bases, considering as eligibility criteria, intervention studies with the population of 18 years and older, of both sexes, published in Portuguese or English Presented as primary outcomes the behavior change for physical activity and/or healthy eating. To codify the studies, the 21-items RE-AIM framework protocol was used to evaluate the impact of programs and interventions in the health area through ve dimensions: outreach, e ectiveness/e ciency, adoption, implementation and maintenance. e studies complied with 61% (n= 16) of the items validated for reach, 40% (n= 11) for effectiveness/eficiency, 17% (n= 4) for implementation, 26% (n= 7) for adoption and 9% (n= 12) for maintenance. No study answered all 21 items of the ve RE-AIM dimensions and 53.8% (n= 14) presented poor quality. Despite the increase in the number of behavioral intervention programs with emphasis on physical activity and / or healthy eating, few studies address the items of RE-AIM dimensions, directly impacting internal and external validity.